2020
DOI: 10.1101/2020.06.15.20131748
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical, immunological and virological characterization of COVID-19 patients that test re-positive for SARS-CoV-2 by RT-PCR

Abstract: Background COVID-19 pandemic is underway. Some COVID-19 cases re-tested positive for SARS-CoV-2 RNA after discharge raising the public concern on their infectivity. Characterization of re-positive cases are urgently needed for designing intervention strategies. Methods Clinical data were obtained through Guangdong COVID-19 surveillance network. Neutralization antibody titre was determined using a microneutralization assay. Potential infectivity of clinical samples was evaluated after the cell inoculation. SAR… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 16 publications
4
57
0
Order By: Relevance
“…Different countries may make slightly different discharge criteria based on their context. The chest CT of one case presented recurrent symptoms with blurred image in the upper lobe of both lungs, more prominent on the left side during the convalescent period, but the severity of image is less than that of late period of hospitalization [108][109][110][111][112][113][114].…”
Section: Discharge Managementmentioning
confidence: 93%
“…Different countries may make slightly different discharge criteria based on their context. The chest CT of one case presented recurrent symptoms with blurred image in the upper lobe of both lungs, more prominent on the left side during the convalescent period, but the severity of image is less than that of late period of hospitalization [108][109][110][111][112][113][114].…”
Section: Discharge Managementmentioning
confidence: 93%
“…This is especially critical at the beginning of an epidemic or when PCR detection systems have to be modified. Moreover, several studies showed that assessing the duration of SARS-CoV-2 infectivity is based on viral cell culture or secondary infection rates [ 12 ],[ 14 ],[ 15 ],[ 16 ],[ 17 ],[ 18 ],[ 19 ]. Therefore, our automated isolation system allows answering this question faster than any other tool, and viral infectivity can be assessed several times during the outbreak to search for modifications, such as reduced transmissibility or effect of antiviral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our automated isolation system allows answering this question faster than any other tool, and viral infectivity can be assessed several times during the outbreak to search for modifications, such as reduced transmissibility or effect of antiviral therapy. Furthermore, the greater the number of strains isolated, the better the understanding of the genetic diversity of this virus, especially since genome sequencing directly from samples is limited to the viral load, and a very poor genome assembly is obtained when the viral load is greater than 19 Ct [ 20 ],[ 19 ]. Subsequently, developing an automated viral isolation technique was necessary to overcome the subjective and time-consuming manual microscopic observations.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Korea on children with SARS‐CoV‐2 infection reported a mean duration of viral shedding in nasopharyngeal swabs of 17.6 days (standard deviation 6 days) 9 . It has been observed that positive RT‐PCR tests in patients with prolonged viral shedding or those who turn positive after a negative RT‐PCR test is due to viral ribonucleic acid (RNA) in dead cells, and these viral particles are inactive and noninfective 10,11 . Persistent SARS‐CoV‐2 positivity has been demonstrated in feces ranging from 1 to 33 days after a negative nasopharyngeal swab 12 .…”
mentioning
confidence: 99%
“…9 It has been observed that positive RT-PCR tests in patients with prolonged viral shedding or those who turn positive after a negative RT-PCR test is due to viral ribonucleic acid (RNA) in dead cells, and these viral particles are inactive and noninfective. 10,11 Persistent SARS-CoV-2 positivity has been demonstrated in feces ranging from 1 to 33 days after a negative nasopharyngeal swab. 12 However, the transmission of SARS-CoV-2 through feces has not been documented.…”
mentioning
confidence: 99%